2021
DOI: 10.7150/ijms.62021
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms of cholesterol elevation aggravating COVID-19

Abstract: Importance: Despite the availability of a vaccine against the severe acute respiratory syndromecoronavirus-2 (SARS-CoV-2), humans will have to live with this virus and the after-effects of the coronavirus disease 2019 (COVID-19) infection for a long time. Cholesterol plays an important role in the infection and prognosis of SARS-CoV-2, and the study of its mechanism is of great significance not only for the treatment of COVID-19 but also for research on generic antiviral drugs. Observations: Cholesterol promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 121 publications
(136 reference statements)
1
20
0
Order By: Relevance
“…Though increased cholesterol levels promote ACE2 and furin trafficking inside host cells 21 , cholesterol plasma levels are found to be decreased in patients post-infection. In brief, high cholesterol present in host cell membrane, virus particles, and human blood may augment the virus entry processing in the host cells 21 , 23 . Our data depicted that geographic locations above 23.5 o N latitude and towards the poles had a higher prevalence of high average total cholesterol levels, often overlapping the areas with the highest COVID-19 cases (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though increased cholesterol levels promote ACE2 and furin trafficking inside host cells 21 , cholesterol plasma levels are found to be decreased in patients post-infection. In brief, high cholesterol present in host cell membrane, virus particles, and human blood may augment the virus entry processing in the host cells 21 , 23 . Our data depicted that geographic locations above 23.5 o N latitude and towards the poles had a higher prevalence of high average total cholesterol levels, often overlapping the areas with the highest COVID-19 cases (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et. al reported the role of cholesterol in increasing the density of ACE2 receptors on host cell membranes 23 . Reports using super-resolution imaging have also observed increased SARS-CoV-2 entry in cells with high blood serum cholesterol levels 40 .…”
Section: Discussionmentioning
confidence: 99%
“…91 In addition, previous reviews suggested that patients with hypercholesterolemia had increased risk for COVID-19 and the related complications. 92 , 93 However, one study compared between two cohorts, namely COVID-19 patients discharged alive and those that died, and multiple regression analysis showed that hyperlipidemia had a protective effect on reducing the likelihood of death (OR=0.75). 94 Another study carried out cluster analysis in a large cohort of 12,066 COVID-19 patients, and the results showed that hyperlipidemia had no significant effects on COVID-19 prognosis.…”
Section: The Correlation Between Hyperlipidemia and Covid-19mentioning
confidence: 99%
“…Furthermore, statins have been found to reduce recovery time and decrease the risk for COVID-19 morbidity and mortality 66,67 . How cholesterol impacts SARS-CoV-2 pathogenesis is currently unclear; however, lipid raft disruption, modification of membrane biophysics, alteration of viral stability and maturation, and immune dysfunction have all been suggested as potential mechanisms [68][69][70] .…”
Section: The Effect Of Sleep Deprivation On Sars-cov-2 Life Cycle Genesmentioning
confidence: 99%